Abaloparatide followed by alendronate in women ≥80 years with osteoporosis: post hoc analysis of ACTIVExtend. Issue 10 (October 2020) - Greenspan, Susan L.; Fitzpatrick, Lorraine A.; Mitlak, Bruce; Wang, Yamei; Harvey, Nicholas C.; Deal, Chad; Cosman, Felicia; McClung, Michael
Abstract: Objective: Fracture risk increases with age, but few studies focus on persons ≥80 years. In the ACTIVE trial, treatment with abaloparatide for 18 months reduced osteoporotic fracture risk and increased bone mineral density. These effects were maintained with 24 months alendronate treatment in ACTIVExtend. We postulated that similar improvements in bone mineral density and safety would be demonstrated in women ≥80 years. Methods: Post hoc analyses of bone mineral density and fracture incidence in women with osteoporosis at high risk of fracture ≥80 years from ACTIVExtend. Results: In total, 56 women aged ≥80 years at ACTIVE baseline entered the ACTIVExtend study; 46 of these completed the study. Mean age was 83.3 years; other baseline characteristics were similar. At the end of ACTIVE, bone mineral density increased at all sites for abaloparatide versus placebo. Bone mineral density increased in parallel in both groups during alendronate therapy (19 to 43 months) in ACTIVExtend. At month 43, mean percent change in bone mineral density from baseline was 17.2% abaloparatide/alendronate versus 8.6% placebo/alendronate ( P  < 0.0001) at the lumbar spine, 5.3% abaloparatide/alendronate versus 3.0% placebo/alendronate ( P  = 0.024) at the total hip, and 4.6% abaloparatide/alendronate versus 3.1% placebo/alendronate ( P  = 0.044) at the femoral neck. Fracture incidence was low and did not differ significantly between groups. Sequential treatment with abaloparatide followed by alendronate was well tolerated; the proportion of participants reporting adverse events was similar between groups. Conclusions: Sequential treatment with abaloparatide followed by alendronate (43 months follow-up) in this small subgroup of ACTIVExtend participants suggests abaloparatide is well tolerated and effective in women aged ≥80 years. N/A: Video Summary: http://links.lww.com/MENO/A618 . Abstract : Supplemental Digital Content is available in the text